Speed Matters in Nordic Hamstring Exercise: Higher Peak Knee Flexor Force during Fast Stretch-Shortening Variant Compared to Standard Slow Eccentric Execution in Elite Athletes - Jesper Augustsson; Tobias Alt; Håkan Andersson (MDPI AG, 2023)
Hamstring strain injuries are prevalent in many sports. Research has demonstrated that the Nordic hamstring exercise (NHE), a knee-dominant exercise addressing the posterior chain muscles, can aid in reducing the risk of hamstring injuries in athletes. However, most research on hamstring injury prevention has focused on performing the eccentric version of the NHE (NHEECC). In contrast, in sports, it is quite frequent for athletes to use an eccentric-concentric version of the NHE. Additionally, eccentric NHE is typically performed using a slow, controlled tempo. The effect of a fast stretch-shortening cycle NHE (NHESSC) compared to standard slow NHEECC on peak knee flexor force has not been investigated. The aim of the study was therefore to investigate fast NHESSC vs. standard slow NHEECC. Our hypothesis posited that peak knee flexor force would be greater for fast NHESSC compared with standard slow NHEECC. The study involved 22 elite athletes (actively competing in both national and international events) consisting of female (n = 10) and male (n = 7) track and field athletes and male football players (n = 5), aged 17-31 years. The participants performed maximum trials of slow NHEECC and fast NHESSC repetitions in which measurement of bilateral peak knee flexor force was conducted at the ankle with the use of a load cell. During the NHEs, a linear encoder was used to measure both the position where the peak knee flexor force was recorded and the average eccentric velocity. SSC contributed to an enhanced NHE performance, where bilateral absolute peak knee flexor force was 13% higher for fast NHESSC vs. standard slow NHEECC (822 vs. 726 N, p < 0.01, ES = 0.54). Participants achieved a 32% greater forward distance at the breakpoint stage during NHEECC compared to the coupling phase for NHESSC (54 vs. 41 cm, p < 0.001, ES = 1.37). Eccentric average velocity was more than three times higher for NHESSC compared with NHEECC (0.38 vs. 0.12 m/s, p < 0.001, ES = 3.25). The key findings of this study were that SSC contributed to an enhanced NHE performance, where absolute peak knee flexor force was 13% greater for fast NHESSC compared to standard slow NHEECC. The fast NHESSC could therefore be an interesting alternative to the standard slow NHEECC execution, as it may offer potential advantages for sprint performance, as well as hamstring injury prevention and rehabilitation.